Epidemiology and Risk Analysis of Malaria among Pregnant Women - S Dhiman; K Yadav; D Goswami; NG Das; I Baruah; L Singh (Tehran University of Medical Sciences, 2012)
Malaria remains a complex problem during the pregnancy, which threatens > 35 millions pregnant women every year. Malaria pathogenesis in pregnancy results in accumulation of infected RBCs in the intervillous spaces causing severe alterations leading to the reduced materno-foetal exchanges. In this article we have revisited the current evidences of clinical implications and overall burden of malaria in pregnancy. Many adverse aftermaths including, low birth weight, intrauterine growth retardation, preterm delivery, stillbirth and anemia were found associated with malaria in pregnant women. Despite of worldwide comprehensive control programmes for malaria in pregnancy, the disease control has been a daunting task everywhere. Socio cultural, economical, lack of awareness and various logistic problems compound the disease in developing countries. Thorough evidence based information and estimates, education and awareness and strengthening of prevention programmes are needed urgently to achieve success in malaria control in pregnancy.